Childhood Imagination in the Autobiographical Novel: “The End I Lived as I Desired” by Waciny Laredj as a Model - Roubach, Jamila (El Omda in Linguistics and Discourse Analysis, 2022)
The art of autobiographical writings is considered as the closest to the spirit of the writer. Retrospectionis a complex mental process linked, in the same time, to the past as a distance instance in time and to the present as the motivator to the process. Retrospection ofchildhood through writing constitutes a challenge in terms of language, structure and choice. The novel "Sirat El Mountaha" toWacinyLaaradjis the best example ofthat Retrospection.The novel "Sirat ElMountaha" toWacinyLaaradjbranches out into titled and numbered fragments that combine into a single narrative passage related to the experiences that the narrator –author- lived in its space in Tlemcen. These spaces accommodate a moment of retrospection.